2011
DOI: 10.1111/j.1472-4642.2011.00862.x
|View full text |Cite
|
Sign up to set email alerts
|

Where are the survivors? Tracking relictual populations of endangered frogs in Costa Rica

Abstract: Aim  We used abiotic environmental variables and historical locality records to infer distributions of endangered anuran species of Costa Rica to promote efficient strategies for future amphibian surveys. Location  Costa Rica. Methods  We used a Maximum Entropy Algorithm (Maxent) to predict potential distribution maps for 17 species of endangered anurans and create a consensus map of species richness. We compared the environmental conditions from localities where relictual amphibian populations were recently r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
25
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 37 publications
2
25
0
Order By: Relevance
“…Furthermore, conducting more seasonal sampling in lowlands will increase the record of presence–absence datasets on Bd and can be used to generate more robust species distribution models (SDMs) from nonopportunistically collected data (Puschendorf et al, ). SDMs can help identify hotspots for future outbreaks of Bd and can be used to predict potential locations for amphibian rediscoveries (García‐Rodríguez et al, ; Puschendorf et al, ). Recent validation surveys have led to the discovery of relict peripheral populations that occur in potential environmental refuges from disease (Puschendorf et al, ; Raffel & Fox, ; Scheele, Hunter, Skerratt, Brannelly, & Driscoll, ), validating increased surveys outside the boundaries of core geographic distributions (Abarca, Chaves, García‐Rodríguez, & Vargas, ; Chaves et al, ; González‐Maya et al, ; Jiménez & Alvarado, ; Nishida, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, conducting more seasonal sampling in lowlands will increase the record of presence–absence datasets on Bd and can be used to generate more robust species distribution models (SDMs) from nonopportunistically collected data (Puschendorf et al, ). SDMs can help identify hotspots for future outbreaks of Bd and can be used to predict potential locations for amphibian rediscoveries (García‐Rodríguez et al, ; Puschendorf et al, ). Recent validation surveys have led to the discovery of relict peripheral populations that occur in potential environmental refuges from disease (Puschendorf et al, ; Raffel & Fox, ; Scheele, Hunter, Skerratt, Brannelly, & Driscoll, ), validating increased surveys outside the boundaries of core geographic distributions (Abarca, Chaves, García‐Rodríguez, & Vargas, ; Chaves et al, ; González‐Maya et al, ; Jiménez & Alvarado, ; Nishida, ).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the focus on highlands for most Bd‐related studies, the few studies conducted in lowlands of Central America have found new locations where this pathogen occurs, suggesting that Bd is more widely distributed than previously thought (Flechas, Vredenburg, & Amézquita, ; Kilburn et al, ; von May, Catenazzi, Santa‐Cruz, & Vredenburg, ; Whitfield et al, ; Whitfield, Kerby, Gentry, & Donnelly, ; Woodhams et al, ; Zumbado‐Ulate et al, ). Predictive models and abiotic suitability for Bd across heterogenous landscapes (Brannelly, Martin, Llewelyn, Skerratt, & Berger, ; García‐Rodríguez, Chaves, Benavides‐Varela, & Puschendorf, ; Puschendorf et al, ; Rödder et al, ) can be generated using available bioclimatic databases such as WorldClim. This dataset contains 19 bioclimatic variables generated by land area interpolations of climate point data from 1950 to 2000.…”
Section: Introductionmentioning
confidence: 99%
“…These findings follow a pattern similar to our finding in that species considered extinct or near-extinct, with recorded massive declines due to chytrid have been rediscovered at previously known locations. Recent analyses suggest that certain areas of Costa Rica have high probabilities of re-discovering populations, and most have not been sampled since 2000 (García-Rodríguez et al, 2012). Our locality is one of these areas which fall within predicted priority regions for surveys and conservation.…”
mentioning
confidence: 96%
“…Usage of presence data to identify landscape factors that are associated with species distribution and to construct habitat suitability maps is an approach increasingly applied in ecology and conservation practice in general (for a review, see Guisan & Zimmermann, 2000), and in the study of endangered amphibians in particular (Blank & Blaustein, 2012;Garc ıa-Rodr ıguez, Chaves, Benavides-Varela, & Puschendorf, 2012). Nevertheless, the performance of such models is poor when sample size is small (Wisz et al, 2008), as is usually the case for rare and elusive species.…”
mentioning
confidence: 99%